Phillip Schuler the remarkable life of one of Australia's greatest war correspondents - Baker, Mark (Allen & Unwin, 2016)
The definitive biography of Phillip Schuler, one of Australia's greatest war correspondents, from Gallipoli to his death in Flanders.